Meningkatkan Kemampuan Berpikir Kritis dan Komunikasi Taruna Akademi Maritim Nusantara Banjarmasin Melalui Pengajaran Debat Bahasa Inggris - Elisa Rosiana; M. Arinal Rahman (BALANTING Jurnal Pengabdian kepada Masyarakat, 2023)
bstractIt has been established that the pedagogical strategy of incorporating discussion into educational settings effectivelysupportsthe growth of critical thinking abilities and strengthens communication skills across various academic settings. This article looks atthe adoption and effects of teaching debate as part of the curriculum for maritime cadets. Maritime cadets are a group of studentscurrently completing training for future careers within the maritime sector. This community service program requiresadopting a collaborative method that works in conjunction with maritime education institutions to provide cadets withtraining in the art of debate. The program results suggest significant improvements in the participants' capacities for criticalthinking and communication, as well as their grasp of issuesrelated to maritime affairs. Thanks to these outcomes, cadets areadequately equipped with key competencies, allowing them to face the complex challenges encountered in the marine area.Keywords: Critical Thinking, Communication, Cadets, Maritime, English Debate